Among the Betrayed - Haddix, Margaret Peterson (New York Simon & Schuster Books for Young Readers, 2002)
Thirteen-year-old Nina is imprisoned by the Population Police, who give her the option of helping them identify illegal "third-born" children, or facing death.
Sequel to: Among the imposters.
690L
81948
Keywords: Betrayal -- Fiction; Conduct of life -- Fiction; Science fiction; Juvenile materials